Anisotropic polarization-induced conductance at a ferroelectric–insulator interface. Issue 12 (December 2018) - Zhang, Yi; Lu, Haidong; Xie, Lin; Yan, Xingxu; Paudel, Tula; Kim, Jeongwoo; Cheng, Xiaoxing; Wang, Hui; Heikes, Colin; Li, Linze; Xu, Mingjie; Schlom, Darrell; et al.
Abstract Coupling between different degrees of freedom, that is, charge, spin, orbital and lattice, is responsible for emergent phenomena in complex oxide heterostrutures1, 2 . One example is the formation of a two-dimensional electron gas (2DEG) at the polar/non-polar LaAlO3 /SrTiO3 (LAO/STO)3–7 interface. This is caused by the polar discontinuity and counteracts the electrostatic potential build-up across the LAO film3 . The ferroelectric polarization at a ferroelectric/insulator interface can also give rise to a polar discontinuity8–10 . Depending on the polarization orientation, either electrons or holes are transferred to the interface, to form either a 2DEG or two-dimensional hole gas (2DHG)11–13 . While recent first-principles modelling predicts the formation of 2DEGs at the ferroelectric/insulator interfaces9, 10, 12–14, experimental evidence of a ferroelectrically induced interfacial 2DEG remains elusive. Here, we report the emergence of strongly anisotropic polarization-induced conductivity at a ferroelectric/insulator interface, which shows a strong dependence on the polarization orientation. By probing the local conductance and ferroelectric polarization over a cross-section of a BiFeO3 –TbScO3 (BFO/TSO) (001) heterostructure, we demonstrate that this interface is conducting along the 109° domain stripes in BFO, whereas it is insulating in the direction perpendicular to these domain stripes. Electron energy-loss spectroscopy and theoretical modelling suggest that the anisotropy of the interfacial conduction is caused by an alternating polarization associated with the ferroelectric domains, producing either electron or hole doping of the BFO/TSO interface. The striped polarization domains in a BiFeO3 /TbScO3 heterostructure induce alternating p- and n-type doping at the interface, giving rise to strongly anisotropic in-plane conductance.